Pombaline reform and the rise of mathematics education to a higher level - Mondini, Fabiane [UNESP]; Viggiani Bicudo, Maria Aparecida [UNESP] (My University, 2018)
The purpose of this research is to understand the orientation given to the teaching of Mathematics, by the Pombaline Reform of 1772, which modifies the statutes of the University of Coimbra, in Portugal. It is a qualitative research, developed in a phenomenological approach, which discusses the reform situated in the socio-historical-political context in which it occurred. This paper presents the changes promoted by the Pombaline Reform during the period in which it was produced and made official, as well as its influence on education, especially with regard to Mathematics. This document elevates this science to the level of upper level course and transforms it into basis for the other sciences. This was an important result, for Mathematics, coming from the Pombalinas Reforms.
As reformas pombalinas e a elevação do ensino de matemática a um curso de nível superior
Keywords: Brazilian Education History; Hermeneutics; Mathematics